2006
DOI: 10.21273/hortsci.41.6.1423
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry (Fragaria ×ananassa Duch.) Growth and Productivity as Affected by Temperature

Abstract: Thermotolerance of photosynthesis and productivity in `Chandler' and `Sweet Charlie' strawberry plants (Fragaria ×ananassa Duch.) exposed to three temperature regimes was studied. Net CO2 assimilation rate (A), variable chlorophyll fluorescence (Fv), efficiency of photosystem II (Fv/Fm), relative chlorophyll content, plant growth, and fruit yield and quality were measured. High temperature (40 °C day/35 °C night) was more detrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 27 publications
5
63
1
1
Order By: Relevance
“…In these plants, there was an increased sensitivity heat stress 7 to 15 days before anthesis, coincident with pollen development. Subjecting plants to a more intense heat stress (generally greater than 4°C above optimum) resulted in severe yield loss extending to complete crop failure (Ghosh et al, 2000;Sato et al, 2000;Kadir et al, 2006;Gote and Padghan, 2009;Tesfaendrias et al, 2010). Tomatoes under heat stress fail to produce viable pollen while their leaves remain active.…”
Section: Annual Cropsmentioning
confidence: 99%
“…In these plants, there was an increased sensitivity heat stress 7 to 15 days before anthesis, coincident with pollen development. Subjecting plants to a more intense heat stress (generally greater than 4°C above optimum) resulted in severe yield loss extending to complete crop failure (Ghosh et al, 2000;Sato et al, 2000;Kadir et al, 2006;Gote and Padghan, 2009;Tesfaendrias et al, 2010). Tomatoes under heat stress fail to produce viable pollen while their leaves remain active.…”
Section: Annual Cropsmentioning
confidence: 99%
“…Studies have shown that when plants are subjected to mild HT stress (1–4°C above optimal growth temperature), there were moderate decreases in yield (Sato, ; Tesfaendrias, McDonald, & Warland, ; Timlin et al., ; Wagstaffe & Battey, ). However, exposure to a more intense HT stress (>4°C above optimum) results in severe yield loss and even complete crop failure (Gote & Padghan, ; Kadir, Sidhu, & Al‐Khatib, ; Sato, Peet, & Thomas, ; Tesfaendrias et al., ). The impacts of HT stress on yield were quantified for major field crops [rice ( Oryza sativa L.), wheat ( Triticum aestivum L.), sorghum ( Sorghum bicolor L., Moench), pearl millet ( Pennisetum glaucum L.…”
Section: Introductionmentioning
confidence: 99%
“…However, exposure to a more intense HT stress (>4°C above optimum) results in severe yield loss and even complete crop failure (Gote & Padghan, 2009;Kadir, Sidhu, & Al-Khatib, 2006;Sato, Peet, & Thomas, 2000;Tesfaendrias et al, 2010). The impacts of HT stress on yield were quantified for major field crops [rice (Oryza sativa L.), wheat (Triticum aestivum L.), sorghum (Sorghum bicolor L., Moench), pearl millet (Pennisetum glaucum L.…”
Section: Introductionmentioning
confidence: 99%
“…Air temperature affects fruit size (Kadir et al, 2006), firmness (Sams, 1999), and skin color (Wang and Camp, 2000); while rainfall decreases SSC and titratable acidity (TA) (Kumar et al, 2011). Generally, environmental factors vary within harvest dates and years, interacting with genotypes (Sims et al, 1997).…”
Section: Introductionmentioning
confidence: 99%